Leaf and shoot apical meristem transcriptomes of quinoa (Chenopodium quinoa Willd.) in response to photoperiod and plant development - Maldonado Taipe, Nathaly (2024)
Understanding the regulation of flowering time is crucial for adaptation of crops to new environment. In this study, we examined the timing of floral transition and analysed transcriptomes in leaf and shoot apical meristems of photoperiod-sensitive and -insensitive quinoa accessions. Histological analysis showed that floral transition in quinoa initiates 2–3 weeks after sowing. We found four groups of differentially expressed genes in quinoa genome that responded to plant development and floral transition: (i) 222 genes responsive to photoperiod in leaves, (ii) 1812 genes differentially expressed between accessions under long-day conditions in leaves, (iii) 57 genes responding to developmental changes under short-day conditions in leaves and (iv) 911 genes responding to floral transition within the shoot apical meristem. Interestingly, among numerous candidate genes, two putative FT orthologs together with other genes (e.g. SOC1, COL, AP1) were previously reported as key regulators of flowering time in other species. Additionally, we used coexpression networks to associate novel transcripts to a putative biological process based on the annotated genes within the same coexpression cluster. The candidate genes in this study would benefit quinoa breeding by identifying and integrating their beneficial haplotypes in crossing programs to develop adapted cultivars to diverse environmental conditions.